2005
DOI: 10.1159/000088869
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Efficacy of Ebastine 20 mg Compared to Loratadine 10 mg and Placebo in the Symptomatic Treatment of Seasonal Allergic Rhinitis

Abstract: Background: Few randomized studies have compared the efficacy of ebastine and loratadine in the symptomatic treatment of seasonal allergic rhinitis (SAR). Methods: A meta-analysis was performed on data from four randomized, double-blind, placebo-controlled, parallel-group clinical trials comparing the efficacy of ebastine 20 mg once daily versus loratadine 10 mg once daily in the symptomatic treatment of SAR symptoms. Primary efficacy variable was the mean change in the overall mean daily reflective total symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…326,327 A recent meta-analysis found ebastine (an agent not available in the United States) superior to loratadine for the decrease in mean rhinitis symptom scores in seasonal allergic rhinitis. 915 Several studies have found cetirizine to be superior to loratadine, although in 1 study, the differences were not statistically significant. 915 In a study of patients with seasonal allergic rhinitis who remained symptomatic after treatment with fexofenadine, azelastine significantly improved total nasal symptom score.…”
Section: Pharmacologic Therapymentioning
confidence: 90%
See 1 more Smart Citation
“…326,327 A recent meta-analysis found ebastine (an agent not available in the United States) superior to loratadine for the decrease in mean rhinitis symptom scores in seasonal allergic rhinitis. 915 Several studies have found cetirizine to be superior to loratadine, although in 1 study, the differences were not statistically significant. 915 In a study of patients with seasonal allergic rhinitis who remained symptomatic after treatment with fexofenadine, azelastine significantly improved total nasal symptom score.…”
Section: Pharmacologic Therapymentioning
confidence: 90%
“…915 Several studies have found cetirizine to be superior to loratadine, although in 1 study, the differences were not statistically significant. 915 In a study of patients with seasonal allergic rhinitis who remained symptomatic after treatment with fexofenadine, azelastine significantly improved total nasal symptom score. 335 The availability of second-generation antihistamines has substantially improved the therapeutic utility of antihistamines, because patients such as older adults who otherwise would avoid antihistamine therapy as a result of sedation or anticholinergic effects can be given antihistamine medications that are favorable for allergic rhinitis management from a risk/benefit standpoint.…”
Section: Pharmacologic Therapymentioning
confidence: 90%
“…We expanded this comparison by selecting studies of other molecules and treatments, including fexofenadine, 49 loratadine, 50 ebastine, 50 ciclesonide, 51 and fluticasone propionate nasal spray. 52 In this descriptive analysis we also reported one of the trials (the largest for population size) included in the metaanalyses of SCIT, 24 mometasone, 10 desloratadine, 35 and montelukast.…”
Section: Indirect Comparison Of Scit Versus Antisymptomatic Treatmentmentioning
confidence: 99%
“…These findings were summarized and discussed by creating systematic reviews and meta-analysis for all antihistamines analysed here. [20][21][22][23][24] In the meta-analysis by Ratner, et al 23 ebastine was compared to loratadine, also an antihistamine from the second generation for the systemic use of allergic diseases. Here ebastine could show a greater decrease in mean rhinitis score from baseline over two and four weeks compared to loratadine and placebo.…”
Section: Discussionmentioning
confidence: 99%